The copyright reward system and content owners in the creative industry: a study of the Malaysian film and TV industry - Alavi, Rokiah; Abdul Ghani Azmi, Ida Madieha (Wiley, 2019)
The creative industry is identified as one of the key drivers to move Malaysia into a high income and knowledge‐based economy. Copyright law and complementary policies were used as measures to stimulate the creative industry. However, the industry's growth is far from the expectation. This leads to a two‐prong inquiry. First, the paper attempts to examine the adequacy of copyright rules and provisions in securing the rights of the creators and provide them with the motivation to produce more creative works. The aim is to explore the dynamics between the various copyright beneficiaries in the creative industry in Malaysia to understand what are the actual problems that deprive the copyright owners from reaping the full value of the exclusive rights granted to them. The second objective is to examine whether the copyright provisions are aligned with complementary policies implemented to boost the creative content industry. Our primary contention is that both the legal reforms and complementary policies used to support the industry need to be revisited. The legal reforms must be aligned with the structure and dynamics of power in the industry to give all the beneficiaries an equal bargaining plane to take advantage of the copyright system.